Lack of Obvious Influence of PLLA Nanofibers on the Gene Expression of BMP-2 and VEGF during Growth and Differentiation of Human Mesenchymal Stem Cells. (2009) - Schofer, Markus D.; Fuchs-Winkelmann, S.; Wack, C.; Rudisile, M.; Dersch, R.; Leifeld, I.; Wendorff, J.; Greiner, A.; Paletta, J. R. J.; Boudriot, U.
Abstract : Growth factors like bone morphogenetic protein 2 (BMP-2) and vascular endothelial growth factor (VEGF) play an important role in bone remodeling and fracture repair. Therefore, with respect to tissue engineering, an artificial graft should have no negative impact on the expression of these factors. In this context, the aim of this study was to analyze the impact of poly(L-lactic acid) (PLLA) nanofibers on VEGF and BMP-2 gene expression during the time course of human mesenchymal stem cell (hMSC) differentiation towards osteoblasts. PLLA matrices were seeded with hMSCs and cultivated over a period of 22 days under growth and osteoinductive conditions, and analyzed during the course of culture, with respect to gene expression of VEGF and BMP-2. Furthermore, BMP-2–enwoven PLLA nanofibers were used in order to elucidate whether initial down-regulation of growth factor expression could be compensated. Although there was a great interpatient variability with respect to the expression of VEGF and BMP-2, PLLA nanofibers tend to result in a down-regulation in BMP-2 expression during the early phase of cultivation. This effect was diminished in the case of VEGF gene expression. The initial down-regulation was overcome when BMP-2 was directly incorporated into the PLLA nanofibers by electrospinning. Furthermore, the incorporation of BMP-2 into the PLLA nanofibers resulted in an increase in VEGF gene expression. Summarized, the results indicate that the PLLA nanofibers have little effect on growth factor production. An enhancement in gene expression of BMP-2 and VEGF can be achieved by an incorporation of BMP-2 into the PLLA nanofibers.